The Effect of Human Capital and Quality of Work Life on Employee Performance Moderated by Organizational Support - Abdan Yahya Fareza; Adya Hermawati; Wahju Wulandari (Journal of Management Research and Studies, 2026)
The purpose of this study is to determine the effect of Human Capital and Quality of Work Life on Employee Performance, moderated by Organizational Support (A Study of Employees at CV. COOL CLEAN in Malang City). The population in this study consists of permanent employees at CV. COOL CLEAN in Malang City. The sampling technique used in this study is “Non-Probability Sampling,” and the sampling method employed is saturation sampling. The sample size for this study is 96 respondents. Data were analyzed using the Smart Partial Least Squares (PLS) software. The results of the study indicate that (1) Better human capital contributes to employee performance. (2) A low quality of work life has not yet contributed to improved employee performance. (3) Better organizational support contributes to employee performance. (4) Increased organizational support has not yet been able to optimize the influence of human capital on employee performance. (5) Organizational support acts as a moderator but has not yet been able to strengthen the influence of Quality of Work Life on employee performance.